CCTV surveillance : analog and digital video practices and technology - Kruegle, Herman (Elsevier Butterworth Heinemann, 2007)
This revision of the classic book on CCTV technology, CCTV Surveillance, provides a comprehensive examination of CCTV, covering the applications of various systems, how to design and install a system, and how to choose the right hardware. Taking into account the ever-changing advances in technology using digital techniques and the Internet, CCTV Surveillance, Second Edition, is completely updated with the recent advancements in digital cameras and digital recorders, remote monitoring via the Internet, and CCTV integration with other security systems. Continuing in the celebrated tradition of the first edition, the second edition is written to serve as a useful resource for the end-user as well as the technical practitioner. Each chapter begins with an overview, and presents the latest information on the relevant equipment, describing the characteristics, features and application of each device. Coverage of aging or obsolete technology is reduced to a historical perspective, and eight brand new chapters cover digital video technology, multiplexers, integrated camera-lens-housing, smart domes, and rapid deployment CCTV systems. * Serves as an indispensable resource on CCTV theory * Includes eight new chapters on the use of digital components and other related technologies that have seen a recent explosion in use * Fully illustrated, the book contains completely updated photographs and diagrams that represent the latest in CCTV technology advancements.